TREATMENT OF SUGAR MANUFACTURING INDUSTRY WASTEWATER BY UPFLOW ANAEROBIC FIXED BED REACTOR AT PRECISE TEMPERATURE - Sivakumar.M.S, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Sugar manufacturing effluent was treated in an anaerobic fixed bed reactor seeded with nongranular anaerobically digested sewage sludge. The ambient room temperature during the study period was between 28-37 oC. Successful reactor starts with granulation was achieved within 90 days of operation. The reactor was started with an OLR of 0.031kgCOD/m3/day and was loaded up to the minimum COD 2240 mg/l. The maximum % COD removal efficiency of 86% for the sugar wastewater at 3.0 days Hydraulic Retention Time with an influent COD concentration of 3960 mg/l was obtained. The VFA concentration gradually decreased from 54mg/l at 3.00 days HRT and at 24mg/l at 0.6 days HRT. The VFA concentration was decreased drastically with increase the HRT. The VSS ranges from 98mg/l to 165mg/l at 0.6day to 3.0days Hydraulic Retention Time. Under steady state conditions the biomass concentration was progressively increased from 98mg/l to 165mg/l to increases the HRT.